Iterative Viterbi algorithm implementation issues. - Lei Wei (IEEE Transactions on wireless communications)
We address several issues for implementing the iterative Viterbi decoder. We show that 3-bit branch metric quantization, 7- or 8-bit state metric precision, and a survivor length of five times the constraint length yields little degradation for the iterative Viterbi algorithm (IVA). Our results show that without changing the VA hardware (except adding some additional circuits), the error performance of several standard systems can be significantly improved.